Type 1 serrated polyposis represents a predominantly female disease with a high prevalence of dysplastic serrated adenomas, without germline mutation in MUTYH, APC, and PTEN genes. Issue 2 (1st April 2016) - Petronio, Marco; Pinson, Stephane; Walter, Thomas; Joly, Marie‐Odile; Hervieu, Valerie; Forestier, Julien; Saurin, Jean‐Christophe
Abstract : Aim: The aim of this article is to clarify the epidemiologic, clinical, endoscopic, biological and genetic characteristics of type 1 serrated polyposis patients. Patients and methods: Consecutive patients responding to the WHO definition of type 1 serrated polyposis in one reference center for polyposis patients accepted genetic counseling. Detailed data on previous endoscopies, histology, and life habits were recorded, after informed consent, germline analysis of MUTYH, APC, and PTEN germline mutations. Molecular biology was tested on available fixed tissue from different lesion types. Results: We included 29 patients (mean age 53.5 years, 21 women (72.4%)), four with a personal history of colorectal cancer (CRC), with a mean of 11.6 SSAs, with associated hyperplastic polyps in 93.1% and adenomas in 82.8%. SSAs showed no dysplasia in 46.9% of lesions (three of 29 patients), LGD in 51.9% (22/29 patients), and HGD in 1.2% (four of 29 patients). Dysplasia was more frequent in proximal SSAs and in women. Colectomy 15 patients (51.7%), upper digestive neoplasms: eight patients (27.5%); smokers: 24 patients (82.8%); family history of CRC: 16 patients (55.2%). Biology: MSI‐H phenotype in one SSA, V600E BRAF mutation in 95% of SSAs; MGMT hypermethylation in three of 17 SSAs. No germline mutation was detected in MYH, APC or PTEN genes. Conclusion: Type 1 serrated polyposis corresponds to a majority of women, with a high prevalence of smokers, a high prevalence of dysplastic serrated adenomas, particularly in females, without identified germline mutation in targeted predisposing genes.